A Transceiver Design Based on an Autoencoder Network for Multi-Color VLC Systems - Dong-Fang Zhang; Hong-Yi Yu; Yi-Jun Zhu; Zhao-Rui Zhu (IEEE Photonics Journal, 2020)
We propose a transceiver design method based on an autoencoder (AE) network for multi-color visible light communication (VLC) systems. Taking into account the chromaticity constraint described by MacAdam ellipses and the peak-value constraint of transmitted signals, the proposed AE network utilizes a peak-value constraint layer and an integrated loss function which different from previous AE designs. The new structure of AE network can be suitable for VLC systems with different numbers of colors. Additionally, noisy channel state information (CSI) is employed during the training of the AE in order to achieve a better performance for the system with imperfect CSI. After training, a transceiver design with the target of minimizing block error rate (BLER) can be obtained, which simultaneously meets the requirements of lighting. The results of numerical simulation experiments demonstrate that our proposed transceiver design outperforms conventional color shift keying (CSK) constellation design in imperfect CSI channel.